Prevalence and Clinical Significance of Psychiatric Comorbidities With Gambling Disorder in 12 Clinical Settings in Japan. Issue 2 (3rd March 2023) - Yamada, Risa; Miyashita, Kumi; Hashimoto, Taka-Mitsu; Hironaka, Naoyuki; Takada, Kohji; Shigeta, Masahiro; Miyata, Hisatsugu
Abstract : Objectives: This study investigated the occurrence rate of psychiatric disorders comorbid with gambling disorder, and their clinical significance in the severity of gambling disorder using a retrospective cross-sectional design. Methods: The medical records of 359 patients (men/women, 326/33; median age, 37.0 years) with gambling disorder as the primary disorder from 12 treatment facilities specializing in addiction (9 clinics and 3 hospitals) in Japan were studied. We investigated patients' comorbid psychiatric disorders, demographic and clinical characteristics, and the severity of gambling disorder based on criteria from the Diagnostic and Statistical Manual of Mental Disorders, fifth edition. Results: Of all patients, 58.3% had comorbidities (tobacco use disorder, 20.9%; alcohol use disorder, 13.9%; major depressive disorder, 13.1%; behavioral addictions, 13.1%; attention-deficit hyperactivity disorder, 6.1%; etc.). Statistical analysis indicated that as the number of comorbid psychiatric disorders increased, psychosocial problems also increased (e.g., proportion of adverse childhood experiences [ P < 0.001], and history of suicide attempts [ P = 0.009]). In the multivariable analysis, behavioral addictions ( β = 0.666; t = 3.151) were significantly associated with gambling disorder severity. Specifically, individuals with gambling disorder comorbid with behavioral addictions including kleptomania, excessive buying, and excessive sex-related behavior may present more severe gambling problems than those without behavioral addictions. Conclusions: Patients with gambling disorder should be carefully assessed for psychiatric comorbidities and interventions should reflect the individual diagnosis.